Penerapan Strategi Interaksi Kelas dalam Pembelajaran Membaca dengan Perspektif Pembelajaran Berdiferensiasi di Sekolah Dasar - Suryanti, Enny; Nugrahani, Farida; Pratiwi, Veronika Unun (Jayapangus Press, 2025)
This study aims to describe the implementation of differentiated classroom interaction strategies in reading instruction for third-grade students at SD Negeri 03 Nglebak, Tawangmangu, and to explain the underlying concept of differentiated learning applied in the process. This research employed a descriptive qualitative approach with data collected through interviews, observations, and document analysis. The findings reveal that the differentiated classroom interaction strategy was implemented by adjusting learning activities to students’ needs, interests, and learning profiles. The teacher grouped students based on their reading proficiency levels and provided varied tasks aligned with each group’s characteristics. Classroom interactions occurred flexibly through small-group discussions, individual guidance, and collaborative work. The differentiated learning practices were grounded in constructivist, humanistic, and multimodal approaches, emphasizing recognition of each student’s unique potential. Evaluation and feedback were provided in diverse forms to allow all students to demonstrate their understanding optimally. This study contributes to strengthening differentiated learning practices in elementary education and supports the development of adaptive classroom interaction strategies responsive to student diversity.